Trends in Fiscal Transparency : Evidence from a New Database of the Coverage of Fiscal Reporting - Wang, Rachel (IMF Working Papers; Working Paper ;, 2015)
Although there are several measures of fiscal transparency, none provides satisfactory information on certain issues of macroeconomic relevance, including whether fiscal data are available for all of general government, whether the government reports a balance sheet, and whether spending and revenue are reported on a cash or accrual basis. Drawing on government finance statistics reported to the IMF, this paper presents a new database of fiscal transparency for 186 countries in 2003-13 and derives from it indices of the overall comprehensiveness of fiscal statistics as well as specific indices of the coverage of public institutions, fiscal flows, and fiscal stocks, respectively. It finds evidence of gradual improvement, most notably in the coverage of institutions, but most countries' reporting remains far from comprehensive.